DEZBATEREA - TEHNICĂ MODERNĂ DE DEZVOLTARE A COMPETENȚELOR DE COMUNICARE ÎN FOS LA STUDENȚII DIN DOMENIUL ȘTIINȚELOR POLITICE - Slobodaniuc, Alina (Editura USM, 2024)
The article addresses the importance of the debate technique in developing communication skills in French for students in political science. In an interconnected and intercultural world, public speaking becomes an essential skill, and debate presents itself as an innovative and stimulating method for learning French. Through the analysis of the concepts of debate and communication skills, the article highlights the benefits of this technique in consolidating knowledge, developing intellectual and linguistic skills, as well as forming an attitude of tolerance and constructive dialogue. Rigorous assessment of linguistic and behavioral aspects in debates highlights the close link between the ability to communicate effectively in a foreign language and success in academic and professional contexts.
Keywords: competență de comunicare; educație lingvistică; educație lingvistică; învățare interactivă; gândire critică; communication competence; language education; interactive learning